Regenerative potential of epicardium-derived extracellular vesicles mediated by conserved miRNA transfer. Issue 2 (18th February 2021) - del Campo, Cristina Villa; Liaw, Norman Y; Gunadasa-Rohling, Mala; Matthaei, Moritz; Braga, Luca; Kennedy, Tahnee; Salinas, Gabriela; Voigt, Niels; Giacca, Mauro; Zimmermann, Wolfram-Hubertus; Riley, Paul Richard
Abstract: Aims: After a myocardial infarction, the adult human heart lacks sufficient regenerative capacity to restore lost tissue, leading to heart failure progression. Finding novel ways to reprogram adult cardiomyocytes into a regenerative state is a major therapeutic goal. The epicardium, the outermost layer of the heart, contributes cardiovascular cell types to the forming heart and is a source of trophic signals to promote heart muscle growth during embryonic development. The epicardium is also essential for heart regeneration in zebrafish and neonatal mice and can be reactivated after injury in adult hearts to improve outcome. A recently identified mechanism of cell–cell communication and signalling is that mediated by extracellular vesicles (EVs). Here, we aimed to investigate epicardial signalling via EV release in response to cardiac injury and as a means to optimize cardiac repair and regeneration. Methods and results: We isolated epicardial EVs from mouse and human sources and targeted the cardiomyocyte population. Epicardial EVs enhanced proliferation in H9C2 cells and in primary neonatal murine cardiomyocytes in vitro and promoted cell cycle re-entry when injected into the injured area of infarcted neonatal hearts. These EVs also enhanced regeneration in cryoinjured engineered human myocardium (EHM) as a novel model of human myocardial injury. Deep RNA-sequencing of epicardial EV cargo revealed conserved microRNAs (miRs) between human and mouse epicardial-derived exosomes, and the effects on cell cycle re-entry were recapitulated by administration of cargo miR-30a, miR-100, miR-27a, and miR-30e to human stem cell-derived cardiomyocytes and cryoinjured EHM constructs. Conclusion: Here, we describe the first characterization of epicardial EV secretion, which can signal to promote proliferation of cardiomyocytes in infarcted mouse hearts and in a human model of myocardial injury, resulting in enhanced contractile function. Analysis of exosome cargo in mouse and human identified conserved pro-regenerative miRs, which in combination recapitulated the therapeutic effects of promoting cardiomyocyte proliferation. Graphical Abstract: